Information systems and networking in universities : an approach - Mohamed Khalil Mohd. Hani 608642; Wan Mohd. Salleh Wan Abu Bakar 213921; JSPS-VCC Seminar on Integrated Engineering (1986 : Penang) 470598 ([S.l.] : [s.n.], 1986)
16